Abundance trends for river macroinvertebrates vary across taxa, trophic group and river typology. Issue 5 (15th December 2022) - Powell, Kathryn E.; Oliver, Tom H.; Johns, Tim; González‐Suárez, Manuela; England, Judy; Roy, David B.
Abstract: There is mounting evidence that terrestrial arthropods are declining rapidly in many areas of the world. It is unclear whether freshwater invertebrates, which are key providers of ecosystem services, are also declining. We addressed this question by analysing a long‐term dataset of macroinvertebrate abundance collected from 2002 to 2019 across 5009 sampling sites in English rivers. Patterns varied markedly across taxonomic groups. Within trophic groups we detected increases in the abundance of carnivores by 19% and herbivores by 14.8%, while we estimated decomposers have declined by 21.7% in abundance since 2002. We also found heterogeneity in trends across rivers belonging to different typologies based on geological dominance and catchment altitude, with organic lowland rivers having generally higher rates of increase in abundance across taxa and trophic groups, with siliceous lowland rivers having the most declines. Our results reveal a complex picture of change in freshwater macroinvertebrate abundance between taxonomic groups, trophic levels and river typologies. Our analysis helps with identifying priority regions for action on potential environmental stressors where we discover macroinvertebrate abundance declines. Abstract : We addressed the question of whether freshwater invertebrates, which are key providers of ecosystem services, are declining in abundance by analysing a long‐term dataset of macroinvertebrates in English rivers. We found a complex picture of change in abundance between taxonomic groups, trophic levels and river typologies. Within trophic groups we detected 19% increases in carnivore abundance, and 14% for herbivores, while estimating decomposers declined by 21.7% since 2002. Trends are heterogeneous across rivers of different typologies, organic lowland rivers having generally higher rates of increase in abundance across taxa and trophic groups, and siliceous lowland rivers having the most declines.